Molecular complexity and diversity of persistent soil organic matter - Andrew R. Jones; Ram C. Dalal; Vadakattu V.S.R. Gupta; Susanne Schmidt; Diane E. Allen; Geraldine E. Jacobsen; Michael Bird; A. Stuart Grandy; Jonathan Sanderman (Soil Biology and Biochemistry, 2023)

Applying population and community ecology theory to advance understanding of belowground biogeochemistry - Robert W. Buchkowski; Mark A. Bradford; Andrew Stuart Grandy; Oswald J. Schmitz; William R. Wieder (Ecology Letters, 2017)
Approaches to quantifying and predicting soil biogeochemical cycles mostly consider microbial biomass and community composition as products of the abiotic environment. Current numerical approaches then primarily emphasise the importance of microbe–environment interactions and physiology as controls on biogeochemical cycles. Decidedly less attention has been paid to understanding control exerted by community dynamics and biotic interactions. Yet a rich literature of theoretical and empirical contributions highlights the importance of considering how variation in microbial population ecology, especially biotic interactions, is related to variation in key biogeochemical processes like soil carbon formation. We demonstrate how a population and community ecology perspective can be used to (1) understand the impact of microbial communities on biogeochemical cycles and (2) reframe current theory and models to include more detailed microbial ecology. Through a series of simulations we illustrate how density dependence and key biotic interactions, such as competition and predation, can determine the degree to which microbes regulate soil biogeochemical cycles. The ecological perspective and model simulations we present lay the foundation for developing empirical research and complementary models that explore the diversity of ecological mechanisms that operate in microbial communities to regulate biogeochemical processes.